Entrepreneurial risk, investment, and innovation - Caggese, Andrea (Journal of Financial Economics, 2012)
I estimate the effect of uncertainty on risky innovation using a panel of 11,417 manufacturing firms. I find that an increase in uncertainty has a large negative effect on the risky innovation of entrepreneurial firms, while it does not have any significant impact on other firms. This negative effect is stronger for the less diversified entrepreneurial firms in the sample. The estimation results are consistent with the innovation dynamics generated in a model in which entrepreneurs are risk averse and cannot diversify the risk of their business.